Seagrass Vegetation Analysis on The Coast of Hadirin and Batu Lawang Beach Karimunjawa National Park - Hasyim, Muhammad Asmuni; Yaqin, Muhammad Ainul; Ulum, M. Bahrul; Hanifa, Berry Fakhry; Cahyono, Teguh (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2019)
The purpose of this study was to determine the structure and condition of seagrass communities in the waters of hadirin Beach and Batu lawang karimunjawa. national park. This exploratory research used descriptive qualitative methods, each study location is divided into two transects. Data identified at SPTN Office 1 Kemujan Karimunjawa National Park. The results of the study were six species of seagrass, namely: Holodule uninervise, Thalassodendron ciliatum, Halophila minor, Syringodium isoetifolium, Thalassia hemprichii and Cymodocea serrulata. The percentage of seagrass cover namely Holodule uninervise is 38.04 %. Thalassodendron ciliatum of 6.25%, Halophila minor of 29.56%, Syringodium isoetifolium of 31.25%, Thalassia hemprichii at 14.21% and Cymodocea serrulata to 16.9%. The highest density of seagrass species in Hadirin Beach is from the Uninervise holodule species 72.30%, with 858 stands on the first transect and 54.66% on the second transect with 253 stands. Whereas for the highest Batu Lawang Beach is the species of Thalassia hemprichii 51.1% with 162 stands, on the first transect and 44.9% with 114 stands. The substrate has the type of sandy clay and coral fragments. Holodule uninervise is the most dominant species found on the beach of Hadirin meanwhile Thalassia hemprichi is the most dominant species in Batu Lawang.